1997
DOI: 10.1291/hypres.20.99
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Patients with "White Coat" Hypertension.

Abstract: To clarify psychological factors related to white coat hypertension, we examined personality characteristics of patients with mild essential hypertension by psychological testing. Patients with essential hypertension were taught to measure their own blood pressure (BP) with a semi-automatic oscillometric BP measuring device and were asked to measure BP at home in the sitting position before going to sleep. The duration of the study was 8 wk. Patients were defined as "white coat" hypertensive patients (WCHT) (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…Previous studies have also concluded that individuals with ICH did not show abnormal hostility, anxiety, or depression, when compared with subjects with sustained hypertension [9][10][11][12]. The study by Muneta et al [10] suggested that subjects with ICH tend to suppress their own emotions and become over-adaptive to their surroundings. Crippa et al [9] suggested that ICH might be associated with healthcare-related fears and emotional instability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have also concluded that individuals with ICH did not show abnormal hostility, anxiety, or depression, when compared with subjects with sustained hypertension [9][10][11][12]. The study by Muneta et al [10] suggested that subjects with ICH tend to suppress their own emotions and become over-adaptive to their surroundings. Crippa et al [9] suggested that ICH might be associated with healthcare-related fears and emotional instability.…”
Section: Discussionmentioning
confidence: 96%
“…There is early evidence that ICH might be associated with healthcare-related fears, suppression of emotions and emotional instability, but not necessarily with anxiety or depression [9][10][11][12]. The findings of these studies have been conflicting and the sample sizes often small.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Critical Parent and Adapted Child were positively correlated with scores of the Zung Self-Rating Depression Scale [16]. In addition, a study using the Egogram Checklist has demonstrated a pattern: Adapted Child is higher than Free Child in patients with "white coat" hypertension, suggesting an over-adaptive attitude among these patients [10]. Moreover, high Adapted Child is associated with dependence and avoidance [8].…”
Section: Discussionmentioning
confidence: 99%
“…Selfrating questionnaire sheets, such as the TEG (Tokyo University Egogram) [8] or Egogram Check List [9], have been widely used in clinical or occupational settings in Japan. There are clinical studies using self-rating egogram in fields of functional somatic syndromes [10,11], psycho-oncology [12], occupational health care [8], and psychiatric disorders (e.g., anorexia and bulimia nervosa) [13]. This is a result of applying a self-rating egogram, TEG to 28 patients with TRD.…”
mentioning
confidence: 99%
“…Harbin 33 em metanálise abrangendo 71 estudos comparativos de reatividade cardiovascular concluiu que homens com personalidade tipo A apresentam reatividade de PA sistólica, consistentemente maior, que homens com personalidade tipo B. Entretanto, testes psicológicos não revelaram diferenças entre indivíduos com HC e hipertensos estabelecidos, no que se refere à depressão, ansiedade, reatividade emocional ou hostilidade 32 , bem como reatividade pressórica a testes de estresse físicos e mentais 34 . Em contrapartida, Munetta e col 35 , utilizando testes psicométricos, concluíram que esses portadores de HC tendem a suprimir suas próprias emoções, tornando-se mais adaptativos ao ambiente, que hipertensos estabelecidos.…”
Section: Hipertensão De Consultório Atualizaçãounclassified